Diversity of staphylococcal cassette chromosome mec (SCCmec) types among methicillin-resistant coagulase-negative staphylococci (MR-CoNS) - Saber, Huda; Jasni, Azmiza; Jamaluddin, T. Z. M. T.; Ibrahim, Rosni (MedCrave Group, 2022)
Methicillin-resistant coagulase-negative staphylococci (MR-CoNS) have become one of the important causes of nosocomial infections yet their clinical data in Malaysia is scarce compared to methicillin-resistant Staphylococcus aureus (MRSA). Staphylococcal Cassette Chromosome mec (SCCmec) genes play roles in their pathogenicity. This study thus aimed to determine species distribution, antimicrobial susceptibility pattern and SCCmec types among MR-CoNS isolated from blood cultures. A laboratory-based descriptive study was involved with non-probability sampling method. One hundred CoNS isolated from blood cultures were collected from Microbiology laboratory, Hospital Serdang and proceeded with phenotypic identification, antimicrobial susceptibility testing, mecA gene detection and SCCmec types classification. Staphylococcus epidermidis was the most common isolated MR-CoNS species. All 100 isolates were resistant to penicillin while being sensitive to vancomycin. The predominant SCCmec Type IV was observed in S. epidermidis which exhibited 100% resistant to penicillin and erythromycin besides dominating multiple antibiotic resistance. Meanwhile, the combination type was observed in type I & IVa (n=9, 9%) whereas 31 strains (31%) were non-typeable. Besides demonstrating MR-CoNS susceptibility pattern variations to commonly used antimicrobials for treatment of staphylococcal infections, this study could also preliminarily contribute in providing more local epidemiological data regarding MR-CoNS.